Analysis Of Mathematical Problem Solving Errors Reviewed From Students' Learning Independence After Implementing The Guided Discovery Learning Model Using Digital Books - Khadijah, Mutiara; Mulyono; Fauzi, Kms. M. Amin; Lumbantobing, Happy (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study looks at 1) the typical math problem-solving mistakes students make using the Newmann procedure after learning with digital books through guided discovery, 2) errors related to how independent students are in their learning, and 3) how independent students are in their learning after using the guided discovery model. Analysis is descriptive in this research. This research included SMPS Dharma Patra grade VIII students. Data analysis indicated that 1) students made the most errors in solving mathematical problems-solving problems based on the Newmann procedure after the guided discovery learning model using digital books was applied: high-category students made encoding errors, and medium-category students made process skill errors and writing errors. 2) Moderate learning independence pupils make 20% transformation mistakes, 80% process skill errors, and 90% writing errors. Students with limited learning independence make 66.67% comprehension errors, 77.78% transformation errors, 100% process skill errors, and 100% final response writing errors. In addition, 36.67% of high-learning independence kids satisfied all criteria. Moderate learning independence students meet four to five markers at 33.34%. Low learning independence students meet one to three markers at 30%.